Peripapillary Nerve Fiber Layer Thickness and Optic Nerve Head Parameters in Patients Recovered from COVID-19: A Longitudinal Study - Mojtaba Abrishami; Kiana Hassanpour; SeyedehMaryam Hosseini; Nasser Shoeibi; Mohammad Reza Ansari-Astaneh; Zahra Emamverdian; Bahareh Gharib; Nasibeh Amini; Majid Abrishami (Journal of Ophthalmology)
Purpose. To quantify the longitudinal changes of the optic nerve head (ONH) parameters and peripapillary retinal nerve fiber layer (pRNFL) thickness in patients recovered from coronavirus disease 2019 (COVID-19) using spectral-domain optical coherence tomography (OCT) analysis. Materials and Methods. In an observational longitudinal study, in patients recovered from COVID-19, ONH OCT images were recorded at least two weeks after recovery from the systemic disease as the baseline and after one and three-month follow-up. Ganglion cell complex (GCC) analysis, ONH parameters, and pRNFL thickness changes were measured. Results. A total of 36 eyes from 18 recovered COVID-19 patients including eleven (61.2%) females were studied. The average age was 35.5 ± 7.5 years. The pRNFL thickness in the nasal lower sector significantly decreased from 77 ± 18 μm in the first post-COVID-19 month to 74 ± 10 μm in the third month (P=0.8). The average, superior, and inferior pRNFL thickness remained unchanged. The average cup volume significantly decreased from 0.27 ± 0.15 mm3 at baseline to 0.19 ± 0.15 mm3 in the third post-COVID-19 visit (P=0.028). In terms of ONH morphologies including rim, disc and cup to disc area, and the vertical and horizontal ratio, the changes were not significant over the 3-month study period. Focal loss volume and global loss volume values were not changed significantly. Conclusion. Localized defect in the nasal lower sector of pRNFL is observed in 3-month post-recovery from COVID-19. Larger studies with longer follow-ups are required to reveal the exact changes in ONH parameters.